Reduction Of Dissolved Ammonia with the Stripper Method in pH and Temperature Variations - Ery Fatarina; Priyono Kusumo; Teodora Maria Fernandes Brito Da silva; Much Yusuf Firdaus (Advance Sustainable Science Engineering and Technology, 2023)
Condensate Polishing System (CPS) regeneration waste from PT. Bhimasena Power Indonesia has an ammonia level of 932 mg N/L. Therefore, research on reducing dissolved ammonia waste is very important. Research gaps in reducing dissolved ammonia waste include the effects of time variations and dissolved ammonia concentrations, the effect of water quality, and the impact of using methods on the environment. The purpose of this study was to determine the effect of variations in pH and temperature on the effectiveness of separating ammonia waste and to obtain optimum pH and temperature values for the separation of dissolved ammonia waste. The method used in this experiment is the stripper method. The results showed that the process of reducing dissolved ammonia using the stripper method reached an optimum value at a temperature of 45 °C and pH 12. Under these conditions, a reduction value of 0.75 mg N/L was obtained. So it can be concluded that the stripper method can reduce dissolved ammonia waste properly. The impact of this research can develop a more effective and environmentally friendly waste treatment method